2014
DOI: 10.1155/2014/626120
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Helps HIV-Positive Women Navigate Social Expectations for and Clinical Recommendations against Childbearing in Uganda

Abstract: Understanding factors that influence pregnancy decision-making and experiences among HIV-positive women is important for developing integrated reproductive health and HIV services. Few studies have examined HIV-positive women's navigation through the social and clinical factors that shape experiences of pregnancy in the context of access to antiretroviral therapy (ART). We conducted 25 semistructured interviews with HIV-positive, pregnant women receiving ART in Mbarara, Uganda in 2011 to explore how access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
1
9
0
2
Order By: Relevance
“… (specific short course antiretroviral regimen not mentioned) 61 PLA (3male, 3 female groups with 8–12 participants): 30 IDIs (16 HIV + &5 HIV – women, 6 HCWs, 3 health officials. **** 8 Kastner, et al 2014 [ 51 ] Uganda: Urban IDIs Women attending HIV clinic for follow up (HIV + pregnant women in their 2ND AND 3RD trimester. (cART) IDIs:25 pregnant women *** 9 *Murithi, et al 2015 [ 41 ] Kenya: IDIs HIV + women pregnant receiving care in a PMTCT clinic.…”
Section: Resultsmentioning
confidence: 99%
“… (specific short course antiretroviral regimen not mentioned) 61 PLA (3male, 3 female groups with 8–12 participants): 30 IDIs (16 HIV + &5 HIV – women, 6 HCWs, 3 health officials. **** 8 Kastner, et al 2014 [ 51 ] Uganda: Urban IDIs Women attending HIV clinic for follow up (HIV + pregnant women in their 2ND AND 3RD trimester. (cART) IDIs:25 pregnant women *** 9 *Murithi, et al 2015 [ 41 ] Kenya: IDIs HIV + women pregnant receiving care in a PMTCT clinic.…”
Section: Resultsmentioning
confidence: 99%
“…A Canadian research has considered as disquieting the poor communication of health professionals as well as how infant feeding in the context of HIV is conducted, especially without the necessary care regarding the social and emotional aspects of the mother (6) . Studies have shown that effective guidelines for women with HIV should start before pregnancy even to address aspects of reproductive health and HIV transmission (26) , and that it has been a challenge to overcome health system weaknesses and…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing social and structural barriers may impact HIV-affected women and couples’ ability to utilize HIV and reproductive health services. For example, optimizing pre-pregnancy maternal health is important for pregnancy planning but may be a lower priority for women, particularly in socio-cultural and normative gendered contexts where pressures and expectations to bear children are high [ 27 ]. Where women have limited autonomy over reproductive decision-making, the delays involved in testing and treating pre-existing conditions or infections before pregnancy attempts occur may create difficulties for women.…”
Section: Discussionmentioning
confidence: 99%